2019
DOI: 10.1101/576322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual recognition of the female body axis drives spatial elements of male courtship in Drosophila melanogaster

Abstract: Like other mating behaviors, the courtship ritual exhibited by male Drosophila towards a virgin female is comprised of spatiotemporal sequences of innate behavioral elements. Yet, the specific stimuli and neural circuits that determine when and where males release individual courtship elements are not well understood. Here, we investigated the role of visual object recognition in the release of specific behavioral elements during bouts of male courtship. By using a computer vision and machine learning based ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…13,[17][18][19][20]23 Besides, specific visual projection neurons have been found to mediate directed courtship. 16,23 Behavioral patterns similar to circling as we define here have been described before in natural 7,18,22,24 or tethered [72][73][74] states in different species. [75][76][77] Under restrained state, earlier studies showed that compromised visual input reduces courtship efficiency, and vision is adequate for the control of courtship tracking 14,72 ; more specifically, both vision and olfaction are implicated in moving behind the female, whereas vision is implicated for courtship near the head.…”
Section: Discussionsupporting
confidence: 60%
“…13,[17][18][19][20]23 Besides, specific visual projection neurons have been found to mediate directed courtship. 16,23 Behavioral patterns similar to circling as we define here have been described before in natural 7,18,22,24 or tethered [72][73][74] states in different species. [75][76][77] Under restrained state, earlier studies showed that compromised visual input reduces courtship efficiency, and vision is adequate for the control of courtship tracking 14,72 ; more specifically, both vision and olfaction are implicated in moving behind the female, whereas vision is implicated for courtship near the head.…”
Section: Discussionsupporting
confidence: 60%
“…7; see Methods). The two optic glomeruli with the most innervation by our WED/VLP cell classes were LC9 and LC11, both containing small object-detecting visual neurons that might be important for courtship behaviors (Bidaye et al, 2020; Keleş and Frye, 2017; McKinney and Ben-Shahar, 2019). The LC9 glomerulus is exclusively innervated by neurons that prefer pulse stimuli whereas the LC11 glomerulus is mostly innervated by neurons that prefer sine stimuli (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…To test if P9 receives excitatory functional inputs from pC1 (Koganezawa et al, 2016) or five LC neural classes implicated in object tracking, courtship or figure detection (Keles ¸and Frye, 2017;Kohatsu et al, 2011;Ribeiro et al, 2018;McKinney and Ben-Shahar, 2018;Aptekar et al, 2015), we monitored responses in P9 by GCaMP6s calcium imaging while optogenetically activating upstream candidates with Chrimson. pC1 or LC9 activation produced reliable calcium transients in P9 (Figures 3B and 3C).…”
Section: P9 Neurons Receive Inputs From Courtship-promoting Neurons and Visual Projection Neuronsmentioning
confidence: 99%